2013
DOI: 10.7314/apjcp.2013.14.8.4571
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Predictors in Taiwanese Survivors with Oral Cancer

Abstract: Background: Depression is a comorbid disabling problem and potentially affects patient likelihood of survival. The aims of this study were to recognize the characteristics of depression and investigate associated predictor factors in patients with oral cancers. Methods: A cross-sectional and correlational design was used to collect data for this study conducted in northern Taiwan. A set of questionnaires was used to measure depression, symptom distress, performance status, social support, and demographic and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Regarding depression, the results of previous studies have also shown that social support has positive effects on the prevention or recovery of depressive symptoms in cancer patients (Imran et al, 2009;Huang and Hsu., 2013;Chen et al, 2013). In addition, we found no any studies that examined the potential relationship between depression and receiving social support among cancer survivors.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding depression, the results of previous studies have also shown that social support has positive effects on the prevention or recovery of depressive symptoms in cancer patients (Imran et al, 2009;Huang and Hsu., 2013;Chen et al, 2013). In addition, we found no any studies that examined the potential relationship between depression and receiving social support among cancer survivors.…”
Section: Discussionmentioning
confidence: 90%
“…Men with histories of long‐term drinking, smoking, and betel nut chewing habits before their cancer was diagnosed may have been affected by a synergistic effect on depression. Since the cancer diagnosis suddenly halted their substance use, this may have led to psychological distress and nicotine withdrawal (Chang et al, 2018; Chen et al, 2013). According to clinical observations, male patients also tend to be less likely to report their feeling and concerns.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Social support has been studied considerably with regard to the psychosocial well-being in cancer populations. The degree of support was found to be correlated with emotional well-being, 20 psychosocial adjustment 21 and quality of life. 22 Although research has shown the benefits of social support in a number of cancer populations, oral cancer is not the same as other cancer patient populations.…”
Section: Introductionmentioning
confidence: 95%